2014
DOI: 10.1016/j.vetpar.2014.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Safety evaluation of orally administered afoxolaner in 8-week-old dogs

Abstract: The safety profile of afoxolaner, a new isoxazoline molecule, was evaluated following the regulatory requirements when administered six times orally in a soft chewable formulation at a dose of at least 1×, 3× or 5× the maximum exposure dose (6.3mg/kg) in 8-week-old Beagle dogs. Thirty-two healthy puppies (16 males and 16 females) were enrolled and allocated randomly to one of four treatment groups. Treatments were administered at three, one-month dose intervals (Days 0, 28 and 56) followed by three, 2-week dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 4 publications
0
20
0
1
Order By: Relevance
“…Safety testing in a study similar to the study described in this article showed that the formulation containing only afoxolaner was safe when administered to dogs between 8 and 24 weeks of age, six separate times at up to 5× the maximum exposure dose (Drag et al ., ). Milbemycin oxime at doses of 2.5, 7.5, and 12.5 mg/kg body weight was proven to be safe to dogs when administered for three consecutive days (Jung et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Safety testing in a study similar to the study described in this article showed that the formulation containing only afoxolaner was safe when administered to dogs between 8 and 24 weeks of age, six separate times at up to 5× the maximum exposure dose (Drag et al ., ). Milbemycin oxime at doses of 2.5, 7.5, and 12.5 mg/kg body weight was proven to be safe to dogs when administered for three consecutive days (Jung et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…An initial clinical assessment of afoxolaner activity against demodectic mange was done with bi-weekly treatments with NexGard at Days 0, 14 and then 28, a strategy based, in-part, on rapidly achieving a steady state of afoxolaner in the blood of the study animals [6]. This was considered to be safe because this schedule was performed in the NexGard and NexGard Spectra target animal safety studies conducted for its registration in the USA and Europe [7] [8]. In those studies, no adverse events related to the treatment were observed during the time that three doses were administered biweekly.…”
Section: Discussionmentioning
confidence: 99%
“…Afoxolaner is an isoxazoline administered monthly to protect dogs against fleas and ticks [NexGard ® (afoxolaner) and NexGard Spectra ® (afoxolaner/milbemycin oxime)] [6] [7] [8]. It is administered at the minimum therapeutic dose of 2.5 mg/kg.…”
Section: Introductionmentioning
confidence: 99%
“…Afoxolaner administered in the palatable NexGard™ (Merial) soft chewable formulation has high bioavailability (73.9%) resulting in fast, consistent absorption and predictable pharmacokinetics (PK) (Letendre et al ., ). The NexGard margin of safety is high and treatment was demonstrated to be safe in puppies given multiple doses of up to 5 times the maximum exposure dose of 6.3 mg/kg (Drag et al ., ). Afoxolaner plasma concentrations are strongly correlated with the efficacy against both fleas and ticks (Letendre et al ., ).…”
Section: Introductionmentioning
confidence: 97%